EXPERIMENTAL PERFORMANCE ANALYSIS OF SOLAR THERMOELECTRIC REFRIGERATOR - Sanket P.Chaudhari; Harshit J. Desai; Gaurav L. Gadhesaria, (International Journal of Advance Engineering and Research Development (IJAERD), 2018)
In the recent years, we have many problems such as energy crises and environmental degradation due to the increasing CO2 emission and ozone layer depletion has become the primary concern. This project utilizes the solar energy for its operation. The solar-powered refrigerator is based on the principle of the thermo-electric module to create a hot side and cold side. The purpose of this project is to make a prototype of portable solar thermo-electric refrigerator to perform experimental performance analysis and to study the performance change when instead of single module two modules are used.